Romeo & Juliet - Shakespeare, William, 1564-1616.; Gill, Roma (Oxford ; New York : Oxford University Press, 2008)
The Oxford School Shakespeare is a well-established series which helps students understand and enjoy Shakespeare's plays. As well as the complete and unabridged text, each playin this series has an extensive range of notes. These include detailed explanations of difficult words and passages, a synopsis of plot and summaries of individual scenes, and notes on the main characters.
Originally published: 1982.
Includes bibliographical references (p. 140-142).
Keywords: Romeo -- (Fictitious character) -- Drama; Juliet -- (Fictitious character) -- Drama; Vendetta -- Drama; Youth -- Drama; Verona (Italy) -- Drama